Flock use of the range is associated with the use of different components of a multi-tier aviary system in commercial free-range laying hens. Issue 2 (3rd March 2020) - Sibanda, T. Z.; Walkden-Brown, S. W.; Kolakshyapati, M.; Dawson, B.; Schneider, D.; Welch, M.; Iqbal, Z.; Cohen-Barnhouse, A.; Morgan, N. K.; Boshoff, J.; Ruhnke, I.
ABSTRACT: 1. The objective of this study was to investigate the association of using a multi-tier aviary system and access to range on flock uniformity in free-range laying hens, and to determine whether the extent of range use or flock uniformity can be predicted from the use of different levels of the aviary system. 2. A total of 13, 716 Lohmann Brown hens from five commercial free-range flocks housed in identical houses on the same farm were individually weighed at 16 weeks of age and allocated to five replicate areas within each house. Hen movement in the multi-tier aviary system and on the range was individually monitored using radio frequency identification (RFID). All hens had access to the range from 18 to 22 weeks of age and were exposed to the same management conditions. 3. Whilst only one flock significantly changed its flock uniformity with time, they differed from each other in uniformity and body weight (P = 0.001). 4. Hens spent most of their available time on the lower aviary tier (7.29 ± 0.029 h/hen/day) and on the upper aviary tier (4.29 ± 0.024 h/hen/day) while the least amount of time was spent on the range and in the nest boxes (0.93 ± 0.005 h/hen/day and 1.48 ± 0.007 h, respectively, P = 0.001). 5. Range use was negatively correlated (r = −0.30) to the time spent on the upper aviary tier and positively correlated (r = 0.46) to the time spent on the lower aviary tier (P = 0.001). Bivariate analysis revealed that range and upper aviary resp. lower aviary tier usage had a significant curvilinear association. 6. In conclusion, the study showed that range use was associated to the time hens spent on the different tiers of the aviary system. Flock uniformity varied between flocks but was not associated with either range and aviary system usage.